1996
DOI: 10.1034/j.1600-0501.1996.070401.x
|View full text |Cite
|
Sign up to set email alerts
|

Recession of the soft tissue margin at oral implants. A 2‐year longitudinal prospective study.

Abstract: The aim of this study was to longitudinally evaluate alterations in the position of the periimplant soft tissue margin, occurring during a 2-year period after insertion of fixed prostheses. 41 patients, subjected to treatment with partial or full-arch implant supported fixed prostheses based on a total of 163 standard Brånemark oral implants, were included in the study. A baseline examination was performed at time of insertion of the prosthetic construction and involved assessments of plaque, mucositis, probin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
253
0
6

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 277 publications
(270 citation statements)
references
References 0 publications
11
253
0
6
Order By: Relevance
“…At the end of the study (6-12 weeks), the barrier epithelium varied between 1.7 and 2.1 mm. These findings corroborated previous clinical results from a longitudinal study (Bengazi et al 1996). Authors evaluated the alterations in the position of the peri-implant soft tissue margin, during a 2-year period follow-up.…”
supporting
confidence: 78%
See 3 more Smart Citations
“…At the end of the study (6-12 weeks), the barrier epithelium varied between 1.7 and 2.1 mm. These findings corroborated previous clinical results from a longitudinal study (Bengazi et al 1996). Authors evaluated the alterations in the position of the peri-implant soft tissue margin, during a 2-year period follow-up.…”
supporting
confidence: 78%
“…Facial soft tissue recession often occurs shortly after abutment connection/crown placement (Bengazi et al 1996, Small & Tarnow 2000, De Rouck et al 2008, but subsequently remains relatively stable during various observation periods (Adell et al 1986, Apse et al 1991, Jemt et al 1994, Bengazi et al 1996, Andersson et al 1998, Scheller et al 1998, Grunder 2000, Priest 2003, Cardaropoli et al 2006, Jemt et al 2006, Rompen et al 2007, De Rouck et al 2008. A thick mucosa (≥1 mm) at the mid-buccal aspect of implants was associated with less mucosal recession compared with a thin mucosa (<1 mm) (zigdon & Machtei 2008).…”
Section: Ii13 Soft Tissue Alterations At Implant-supported Restoratmentioning
confidence: 99%
See 2 more Smart Citations
“…5, 7 However , this has been disputed. [2][3][8][9] One study 6 reported a correlation between the presence of keratinized tissue, plaque levels and the incidence of mucositis, and theorized that sites with minimal keratinized tissue might be prone to a lower incidence of periodontal pocket formation. 3,10 In the anterior maxilla, however, the contribution of thick, keratinized gingiva to implant esthetics has not been disputed.…”
Section: Introductonmentioning
confidence: 99%